Decadal climate predictions for the period 1901–2010 with a coupled climate model. Issue 6 (28th March 2014) - Müller, W. A.; Pohlmann, H.; Sienz, F.; Smith, D.
Abstract An ensemble of yearly initialized decadal predictions is performed with the Max Planck Institute Earth System Model to examine the forecast skill for the period from 1901 to 2010. Compared to the more recent period (1960 to present day), the extended period leads to an enlargement of regions with significant anomaly correlation coefficients (ACC) for predicted surface temperatures. This arises from an increased contribution of the trend, which is also found in the uninitialized runs. Additionally, in the North Atlantic decadal variability plays a larger role over the extended period, with detrended time series showing higher ACC for the extended compared to the short period. Furthermore, in contrast to the uninitialized simulations, the initialized predictions capture the North Atlantic warming events during the 1920s and 1990s, together with some of the surface climate impacts including warm European summer temperatures and a northward shift of Atlantic tropical rainfall.